PENGETAHUAN ORANG MUNA TENTANG SUMBER AIR BERSIH DARI PEPOHONAN - Ruslin Ruslin; Wa Ode Sifatu; Ashmarita Ashmartia (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2018)
This study aims to determine the knowledge and methods of extracting clean water from trees in Munanese in Wuna Village, District of Tongkonu, Muna Regency. This study uses a qualitative method with data collection techniques through observation and in-depth interviews. The results of this study indicate that since ancient times Munanese has had local knowledge about the process of extracting clean water from trees called